Assessment of the socio-economic impacts of Tourism on three rural communities neighbouring Addo Elephant National Park, Eastern Cape, South Africa - Mlungu Fezeka; Kwizera Alice Stella (African Journal of Hospitality, Tourism and Leisure, 2020)
This paper examines the extent to which three local communities neighbouring Addo Elephant National Park (AENP) have benefitted from the tourism development and business activities in the park in terms of women and youth empowerment, business and job opportunities, skills development and other people and community development. The paper further examines the relationship between communities and AENP with its concessionaires, and the pros and cons of private sector involvement in a public park. Data for the study was gathered from 42 participants through observation, document review, key informant interviews with AENP officials, Municipal officials and Community Trust personnel; and focus group discussions with members of three participating communities, namely: Colchester, Valentia and Nomathamsanqa. Participants were selected purposively. Local beneficiation was generally found to be minimal characterised by exclusion of black Africans from concessionary agreements; marginalisation of women in business contracts which are in any case typically low income and short term; inequalities in entrepreneurship and other local community development support (and funding); lack of consultation and communication with communities, particularly regarding their own development; inconsistencies in and misguided funding of development projects, including skills development not tailored towards people’s needs; low wage employment opportunities; and undemocratic rather than humanist approaches to people development, among others. This defies Sustainable ethical tourism development principles.